Turning yerba mate waste into high-performance lithium–sulfur battery cathodes - Tesio, Alvaro Yamil (2023)
In this study, a non-activated carbon (YMCsingle bondC) derived from waste yerba mate was examined as a matrix for the development of a carbon‑sulfur composite cathode (YMC-C@S). The carbonaceous material is produced through a simple process of pyrolyzing extracted cellulose from residual yerba mate, avoiding costly and complex stages of chemical activation or additional purification. Due to its high carbon content and mesoporous structure, YMC-C can serve as an effective host for sulfur. After adding 70 % sulfur via the melt diffusion method, the YMC-C@S composite shown a remarkable initial capacity of 1678 mAh gS−1 as a cathode material, along with high reversible capacity at a low charge/discharge rate. Additionally, even when subjected to an increased C-rate during long cycling, discharge capacities at 1C of 777 mAh gS−1 and 674 mAh gS−1 after 165 cycles demonstrate good rate capability. When the cycling protocol is optimized, the YMC-C@S composite exhibits very low loss of capacity per cycle, even when using fast charge stages. The efficacy of YMC-C as an efficient cathode material in LSB is confirmed by the positive results of a self-discharge test conducted over a period of 7.5 months.